Semantic triads in Russian discourse. - GRDZELYAN, ROUZAN (Bulletin of Yerevan University H: Russian Philology, 2021)
The article is devoted to the field of modern semasiology, which is aimed at identifying the semantic layers of linguistic units. Such semantic layers to some extent affect the formation of grammatical forms and the emergence of mechanisms. Data from similar studies can be useful in creating functional grammar.